Knee Arthodesis, as a salvage procedure for Non-union of floating knee after ilizarov fixation-A case report - Harsh Kumar; Raj Suhas Kamble; Suhas Laxman Kamble (Journal of Orthopaedic Case Reports)
Introduction: The Ilizarov technique is a widely used method for managing complex fractures, especially those involving periarticular regions such as the distal femur and proximal tibia. Ilizarov is a versatile process which can also be used for limb lengthening, deformity correction and for septic and aseptic non-unions. Case Report: We present the case of 48-year-old male with non-union of proximal tibia and distal femur fracture with Ilizarov in situ. A floating knee on the right side was unsuitable for open reduction and internal fixation due to poor skin health. Ilizarov fixation was planned for the patient. This instance demonstrates the difficulties associated with floating knee. The technique’s limits in treating specific periarticular fractures are highlighted by the Ilizarov fixation’s failure in this instance. Conclusion: An efficient salvage technique that provides permanent pain relief and functional stability is knee arthrodesis. The need of customized treatment planning in handling complicated fracture situations is highlighted by this example.